Dynamic modeling and vibration characteristics analysis of parallel antenna - G. Zhang; J. He; J. Guo; X. Xia (Mechanical Sciences, 2022)
Research on the vibration characteristics of the mechanical systems is a necessary step for the stable and reliable operation of high-end equipment. The 6 degrees of freedom parallel mechanism is proposed for the supporting mechanism of the antenna. First, the dynamic equations of the moving platform and branch of the mechanism are established. The closed-form dynamics of the mechanism are derived based on the Newton–Euler method. In addition, the vibration equation of the parallel antenna is established based on the vibration theory, and the relationship between the natural frequency, displacement response, and vibration frequency is obtained. Afterward, the pitch and roll poses of a 1.8 m aperture antenna are developed based on a MATLAB software simulation. The actuation forces of parallel antenna under no-load and load conditions are simulated. Finally, the natural frequencies and vibration modes of the initial position and roll (20∘) are simulated based on the Adams software vibration analysis module. Furthermore, the relationship between the displacement response of the moving platform and the resonant frequency is studied based on the harmonic response analysis. The control strategy based on the dynamic model improves the control accuracy of parallel antenna. This research work provides a guarantee for the dynamic characteristics analysis and engineering application of parallel antenna.